A STUDY ON MICRO BUBBLES AERATION METHOD ON WATER TURBIDITY AT AQUACULTURE EARTHEN PONDS UNDER DIFFERENT OPERATIONAL PARAMETERS - Tarek FOUDA; Abd-Elrahman ELRAYES; Abd-Elhameed ELHANAFY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The experiment was established at an earthen aquaculture private farm in Kafrelshikh Government, Egypt. During 2021. To study the effect of operational variables at tube diffusion aeration system on turbidity values corresponding to Secchi disk clarity. Experimental variables under study were five air flow rates (0.1, 0.18, 0.23, 0.28 and 0.33 m3.h-1), three tube wall thickness (4, 6 and 7 mm), three tube depth from water surface (0.3, 0.50 and 0.70 m) and two design shapes for aeration system (circular and Longitudinal). Aeration system consist of circular tube holder, an electric single-phase compressor, three models of rubber diffusion tubes (D25-4, D25-6 and D25-7), portable galvanic dissolved oxygen meter, Secchi disk, digital LCD anemometer and thermometer and digital vernier. The results showed that, the lowest value for Secchi disk clarity were 7 cm obtained at operational conditions of 0.33 m3.h-1 air flow rate, 0.70 m depth from water surface, 4 mm thickness of tube wall and circular shape design. While, the highest value for Secchi disk clarity were 41 cm obtained at operational conditions of 0.10 m3.h-1 air flow rate, 0.30 m depth from water surface, 7 mm thickness of tube wall and Longitudinal shape design. The permissible variables limits were (0.1, 0.18 and 0.23 m3.h-1) for air flow rate, (4, 6 and 7 mm) for tube wall thickness, (0.3, 0.50 and 0.70 m) for tube depth from water surface and both of (circular and Longitudinal) design shapes.